Synergistic anti-tumor effects of lenalidomide and gefitinib by upregulating ADRB2 and inactivating the mTOR/PI3K/AKT signaling pathway in lung adenocarcinoma: Role of ADRB2 and mTOR/PI3K/AKT in LUAD - Zhou, Shuangshuang; Deng, Meiyi; Bian, Xuyu; Shi, Jindong; Liang, Rongrui; Tao, Min (Cellular and Molecular Biology, 2024)
Gefitinib is commonly used to be the first-line therapy for advanced non-small cell lung cancer (NSCLC). Therapeutic effect of gefitinib is reduced due to acquired resistance, and combined treatment is recommended. In this research, we planned to explore the impacts of combined treatment of lenalidomide and gefitinib on gefitinib-sensitive or -resistant NSCLC cells. The co-treatment results demonstrated that enhanced antitumor impact on NSCLC cell growth, migration, invasion, cell cycle process and apoptosis. The tumor-bearing mouse models were established using PC9/GR cells. In vivo assays also showed that lenalidomide and gefitinib synergistically inhibited mouse tumor growth along increased the survival of mice. ADRB2 was identified as a lowly expressed gene in PC9/GR cells and LUAD tumor tissues. LUAD patients with high ADRB2 expression were indicated with favorable survival outcomes. Moreover, ADRB2 was upregulated in lenalidomide and/or gefitinib-treated PC9/GR cells. ADRB2 deficiency partially offsets the suppressive impacts of lenalidomide and gefitinib co-treatment on the viability and proliferation of PC9/GR cells. Additionally, lenalidomide and gefitinib cotreatment significantly inactivated the mTOR/PI3K/AKT signaling pathway compared with each treatment alone. Rescue assays were performed to explore whether lenalidomide and gefitinib synergistically inhibited the growth of PC9/GR cells via the PI3K/AKT pathway. PI3K activator SC79 significantly restored reduced cell proliferation, migration and invasion along with elevated cell cycle arrest and apoptosis caused by lenalidomide and gefitinib cotreatment. In conclusion, lenalidomide and gefitinib synergistically suppressed LUAD progression and attenuated gefitinib resistance by upregulating ADRB2 and inactivating the mTOR/PI3K/AKT signaling pathway in lung adenocarcinoma.